Determination of strobilurin fungicides in cotton seed by combination of acetonitrile extraction and dispersive liquid−liquid microextraction coupled with gas chromatography. Issue 7 (27th February 2014) - Xue, Jiaying; Li, Huichen; Liu, Fengmao; Jiang, Wenqing; Chen, Xiaochu
<x xml:space="preserve">Abstract</x> The simultaneous determination of four strobilurin fungicides (picoxystrobin, kresoxim‐methyl, trifloxystrobin, and azoxystrobin) in cotton seed by combining acetonitrile extraction and dispersive liquid−liquid microextraction was developed prior to GC with electron capture detection. Several factors, including the type and volume of the extraction and dispersive solvents, extraction condition and time, and salt addition, were optimized. The analytes were extracted with acetonitrile from cotton seed and the clean‐up was carried out by primary secondary amine. Afterwards, 60 μL of n‐hexane/toluene (1:1, v/v) with a lower density than water was mixed with 1 mL of the acetonitrile extract, then the mixture was injected into 7 mL of distilled water. A 0.1 mL pipette was used to collect a few microliters of n‐hexane/toluene from the top of the aqueous solution. The enrichment factors of the analytes ranged from 36 to 67. The LODs were in the range of 0.1 × 10−3−2 × 10−3 mg/kg. The relative recoveries varied from 87.7 to 95.2% with RSDs of 4.1−8.5% for the four fungicides. The good performance of the method, compared with the conventional pretreatments, has demonstrated it is suitable for determining low concentrations of strobilurin fungicide residues in cotton seed.